Development of coordination abilities as the foundations of technical preparedness of rugby players 16-17 years of age - Rovnyi, A.; Paskov, V.; Nesen, O.; Tso, A.; Ashanin, V.; Filenko, L.; Karpets, L.; Goncharenko, V. (Journal of Physical Education and Sport, 2018)
Purpose: substantiation and development of a methodology for developing the coordination abilities of rugby players of 16-17 years as the basis of technical readiness. Material and methods of research: 30 rugby players aged 16-17 who participated in the Junior Championship of Ukraine participated in the study. A special program of coordination training was developed, which contributed to the manifestation of technical preparedness in the difficult competitive conditions of the rugby team. The level of influence of coordination abilities on technical preparedness was determined by the correlation coefficient between these indicators. Result: a special program for the development of coordination abilities for rugby players aged 16-17 was developed, which included a system of exercises aimed at increasing vestibular stability, accuracy of reproduction of traffic parameters after various abrupt stops, rotations and confrontations of athletes of the opposing team. Indicators of tests of coordination abilities reliably correlate with indicators of technical preparedness of athletes. Conclusion: conducted researches made it possible to justify the necessity of introducing these parameters of the program, which are based on adaptive regularities of the athlete's body systems to physical loads and reliably correlate with the indicators of technical readiness.